(untitled) (Nigerian Journal of Technology, 2017)
This paper deals with the steady and dynamic states analysis of induction motor using finite element analysis (FEA) approach. The motor has aluminum rotor bars and is designed for direct-on-line operation at 50 Hz. A study of the losses occurring in the motor performed at operating frequency of 50Hz showed that stator copper loss and rotor copper loss were higher than the other types of losses like the stray, iron core, frictional and windage losses. The motor efficiency based on material design was also studied at operating temperature. The materials considered in this paper are iron, nickel and cobalt. It was observed that iron at 75°C provided the best efficiency than other materials. The steady and dynamic states characteristics of the motor at rated load and on no-load conditions were observed. The flux levels at these loading conditions were also monitored. http://dx.doi.org/10.4314/njt.v36i4.29